PERANAN KEPALA DINAS KESEHATAN DALAM PENGAWASAN PROGRAM JAMKESMAS DI KABUPATEN HALMAHERA UTARA - Tidore, Sermi (ACTA DIURNA KOMUNIKASI, 2013)
Efforts to improve the implementation of the program has been carried out by the government JAMKESNAS, but still there are problems or irregularities implementation of health services to participants in both health card and Hospital Health Center. This was caused partly by a lack of oversight of the implementation of the program at the hospital or health center .. Based on this conceptual background, this study was conducted to determine the extent to which the role of the health department in the monitoring program in North Halmahera JAMKESMAS. The method used in this study is a qualitative method. The focus of this research is the head of health supervision in the implementation of a health card services in hospitals and health centers. Source of data / key informants in the study were taken from various elements associated with the implementation of the existing health card program in the health department, hospitals, health centers, and PT.ASKES; than that taken from the participants JAMKESNAS informants to determine service delivery in health centers and hospitals. The total number of data sources / informants, there were 14 people. The main instrument of this study is the researchers themselves, while the technique of data collection was interviews. The analysis technique used is the qualitative analysis of interactive models and Hubermann Miler. The results lead to the conclusion that in general health services in the District of North Halamahera in katakana yet effective due to the current resource (Doctor), respectively in hospitals and even health centers is still low: conclusions based on research indicators, namely: (1) The role of the head of health in direct supervision method jamkesmas program can be conducted in accordance with both the position and authority as a responsible team manager and secretary jamkesmas jamkesmas district coordination team, (2) the role of head of the health card program oversight through monitoring method does not lanagsung (coordination and reporting system) in hospitals and health centers of North Halmahera regency has been implemented effectively. Departing from the results of this penellian then suggested: (1) the role of the health card program oversight through direct supervision method needs to be done by the head of North Halmahera district health offices. (2) the role of head of department in the supervision of a health card program through the method of indirect supervision (coordination and reporting system) needs to be improved. Keywords: monitoring, health card program, health services.